Concurrent Germline and Somatic Mutations in FLCN and Preliminary Exploration of Its Function: A Case Report - Wang, Tao; Yang, Yang; Feng, Huayi; Cui, Bo; Lv, Zheng; Zhao, Wenlei; Zhang, Xiangyi; Ma, Xin (Frontiers in Oncology, 2022)
Birt–Hogg–Dube syndrome is an autosomal dominant condition that arises from germline folliculin (FLCN) mutations. It is characterized by skin fibrofolliculomas, lung cysts, pneumothorax, and renal cancer. Here, we present the case of a 36-year-old woman with asymptomatic, multiple renal tumors and a history of spontaneous pneumothorax. Genetic analysis revealed a hotspot FLCN germline mutation, c.1285dupC (p.H429fs), and a novel somatic mutation, c.470delT (p.F157fs). This information and the results of immunohistochemical analysis of the renal tumors indicated features compatible with a tumor suppressor role of FLCN. Two transcription factors, oncogenic TFEB and TFE3, were shown to be regulated by FLCN inactivation, which results in their nuclear localization. A potential relationship between FLCN mutation and ciliary length was also examined. We showed that a deficiency in the tumor suppressor FLCN leads to deregulation of the mammalian target of rapamycin signaling pathway. Thus, the new somatic mutation identified in our patient provides novel insights into the relationship among FLCN mutations, TFEB/TFE3, and cilia. However, an in-depth understanding of the role of folliculin in the molecular pathogenesis of renal cancer requires further study.